La valoración de documentos en las universidades portuguesas y brasileñas - Bizello, Maria Leandra [UNESP] (My University, 2016)
Record appraisal in the brazilian and Portuguese university environments is analysed comparatively in light of the Canadian archival theory and the post-custodial reflection developed in Portugal, beyond the influence of these theories in the conception of archival systems. Especifically, São Paulo state universities (USP, UNICAMP and UNESP) and Portuguese universities were studied. Universities have a peculiar context regarding the production of administrative and scientific documents that reflects their activities and functions. This study focuses on the context of record creation in universities to how how their records are produced and managed.
Document appraisal in Portuguese and Brazilian universities
Keywords: Appraisal; Brazil; Portugal; Records management; Universities; University archives